Optimizing voltage profile and mitigating power losses in distribution network reconfiguration via the integration of distributed generation penetration in Malaysia - Othman, Ahmad Fauzi; Othman, Mohammad Lutfi; Ab Kadir, Mohd Zainal Abidin; Abdul Wahab, Noor Izzri; Zainul Abidin, Aidil Azwin (Semarak Ilmu Publishing, 2025)
Radial distribution networks face challenges such as voltage drop and power losses, which are significant concerns. The objective of reconfiguration in a distribution network is to determine the optimal combination of switching system branches that maximizes a specific goal function while adhering to defined limitations. This process improves the quality of electrical power and enhances the performance of the distribution network. This research paper presents optimal techniques for optimizing the reconfiguration of the distribution system and the installation of DG units to minimize active power losses and improve the bus voltage profile. These techniques are based on technical analysis conducted using the Power System Study ADEPT (PSS ADEPT) software in an industrial setting. The load flow calculations are performed using technical analysis technique simulated by PSS ADEPT. The proposed methods are evaluated in the distribution system of the 145-bus test system. Furthermore, the distribution system model incorporates the solar DGs and load profile. The simulation results demonstrate the effectiveness of the proposed method in reducing active power losses and improving the system bus voltage. Additionally, it successfully addresses the system reconfiguration problem and enhances the performance of the distribution system. These improvements are particularly advantageous when integrating distributed generation (DG) into the distribution network to accommodate load growth over the next 5 years. The results confirm the effectiveness and success of the proposed methodology in determining the most suitable placement and dimensions of solar distributed generators (DGs) to minimize power losses and enhance voltage profiles.